Reading Profile of Grade 10 Learners: A Case Study - Marilou D. Ferreras; Susan F. Astillero (Journal of General Education and Humanities, 2025)
This study explored the reading difficulties of Grade 10 students with the objectives of describing their reading profiles, identifying factors affecting their reading profile, and proposing a relevant output based on the results of the study. The research addressed the problem of persistent reading challenges among secondary learners despite prior literacy instruction. A qualitative case study method was employed. Data were collected using the Rapid Literacy Assessment, unstructured interviews, and classroom observations from five purposefully selected student participants. Results showed that substitution errors were the most frequent reading miscues. These were followed by omission, repetition, and reversion. The analysis further identified key factors affecting the participants' reading profiles. These include socio-economic constraints, minimal parental involvement, psychological barriers, observed reading behaviors, and delayed literacy development. In response, a tailored reading workbook was developed to address the student’s specific decoding and fluency needs. The study emphasized the importance of focused interventions that target both technical and affective aspects of reading. It is recommended that schools enhance parental engagement and increase access to reading materials. The developed workbook is suggested as supplementary material to support struggling readers and improve literacy instruction in similar contexts.